Modified Broström technique for repair of the lateral ankle ligament complex: Narrative review - Silva, Leidiane Santos (Journal of the Foot & Ankle, 2025)
Objective: To evaluate the effectiveness of anatomic repair of the lateral ankle ligament complex, with emphasis on the anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL), using the modified Broström technique, specifically the Gould modification and contemporary variants (e.g., capsular reinforcement, inferior extensor retinaculum, and suture‑tape augmentation). Methods: Narrative review conducted in PubMed/MEDLINE, SciELO, LILACS, Web of Science, and Scopus databases, using search terms related to ankle instability, Broström technique, and ligament reconstruction. Studies published in Portuguese, English, and Spanish were included, without date restrictions, presenting data on clinical and functional outcomes. Results: Included studies showed significant improvement in functional scores, especially in the AOFAS score, after anatomic repair. The findings indicate high success rates for the technique, with reduced recurrence of instability, improved strength and joint mobility, and high patient satisfaction. Comparison with other surgical techniques suggests that the modified Broström technique has equivalent or superior clinical outcomes with lower morbidity. Conclusion: The modified Broström technique is effective for anatomic repair of the lateral ankle ligament complex, promoting functional recovery and joint stability in patients with chronic lateral instability. Despite the methodological limitations of the available studies, the findings support the clinical relevance of the procedure and its role as the first line surgical option in appropriately selected cases. Level of evidence V; Expert opinion.